ChemInform Abstract: Depolymerization of Cellulose to Processable Glucans by Non‐Thermal Technologies. Issue 36 (August 2016) - Jerome, F.; Chatel, G.; De Oliveira Vigier, K.
Abstract: Review: [60 refs.